Epidemiology of candidemia: 3-year results from the emerging infections and the epidemiology of Iowa organisms study. - Diekema, D; Messer, SA; Brueggemann, A; Coffman, S; Doern, G; Herwaldt, L; Pfaller, M (2002)
Bloodstream infections due to Candida species cause significant morbidity and mortality. Surveillance for candidemia is necessary to detect trends in species distribution and antifungal resistance. We performed prospective surveillance for candidemia at 16 hospitals in the State of Iowa from 1 July 1998 through 30 June 2001. Using U.S. Census Bureau and Iowa Hospital Association data to estimate a population denominator, we calculated the annual incidence of candidemia in Iowa to be 6.0 per 100,000 of population. Candida albicans was the most common species detected, but 43% of candidemias were due to species other than C. albicans. Overall, only 3% of Candida species were resistant to fluconazole. However, Candida glabrata was the most commonly isolated species other than C. albicans and demonstrated some resistance to azoles (fluconazole MIC at which 90% of the isolates tested are inhibited, 32 microg/ml; 10% resistant, 10% susceptible dose dependent). C. glabrata was more commonly isolated from older patients (P = 0.02) and caused over 25% of candidemias among persons 65 years of age or older. The investigational triazoles posaconazole, ravuconazole, and voriconazole had excellent in vitro activity overall against Candida species. C. albicans is the most important cause of candidemia and remains highly susceptible to available antifungal agents. However, C. glabrata has emerged as an important and potentially antifungal resistant cause of candidemia, particularly among the elderly.